Randomised, double-blind, placebo-controlled trial to determine whether steroids reduce the incidence and severity of nephropathy in Henoch-Schönlein Purpura (HSP). Issue 10 (11th July 2013) - Dudley, Jan; Smith, Graham; Llewelyn-Edwards, Anne; Bayliss, Kate; Pike, Katie; Tizard, Jane
Abstract : Background: The long-term prognosis of Henoch-Schönlein Purpura (HSP) is predominantly determined by the extent of renal involvement. There is no consensus as to whether treatment with prednisolone at presentation can prevent or ameliorate the progression of nephropathy in HSP. Methods: Children under 18 years of age with new-onset HSP were randomly assigned to receive prednisolone or placebo for 14 days. The primary outcomes were (a) the presence of proteinuria at 12 months (defined as urine protein : creatinine ratio (UP : UC) >20 mg/mmol) and (b) the need for additional treatment (defined as the presence of hypertension requiring treatment or renal biopsy anomalies or the need for treatment of renal disease) during the 12 month study period. Results: 352 children were randomised. Of those patients with laboratory UP : UC results available at 12 months, 18/123 (15%) patients on prednisolone and 13/124 (10%) patients on placebo had UP : UC >20 mg/mmol. There was no significant difference in the proportion of patients with UP : UC >20 mg/mmol at 12 months between the treatment groups (OR (prednisolone/placebo)=1.46, 95% CI 0.68 to 3.14, n=247), even after adjusting for baseline proteinuria and medications known to affect proteinuria (adjusted OR=1.29, 95% CI 0.58 to 2.82, n=247). Similarly, there was no significant difference in the time needed for additional treatment between the two groups (hazard ratio (HR) (prednisolone/placebo)=0.53, 95% CI 0.18 to 1.59, n=323). Conclusions: This is the largest trial of the role of steroids in children with HSP. We found no evidence to suggest that early treatment with prednisolone reduces the prevalence of proteinuria 12 months after disease onset in children with HSP. Trial registration Number: ISRCTN71445600